Management Model of Village Owned Enterprises (BUMDes) - Kartib Bayu; Sri Hartati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Village Owned Enterprises (BUMDes) are business entities whose capital is wholly or largely owned by the village through direct equity participation from village assets. BUMDes as an economic institution with business capital is built on community initiatives and adheres to the principle of independence. The approach method in completing the program is the individual approach, institutional group approach and the library approach. Based on the results of the activities, it was found that (1) Exploration of Bumdes business potential must pay attention to local resources and the competence and commitment of the village community. (2) Bumdes Business Management must be able to integrate community businesses (UMKM) with Bumdes Businesses that are mutually supportive and mutually beneficial. (3) Bumdes business development is carried out in an integrated, synergistic and integrated manner from various stakeholders in one rural area.